The role of traditional cardiovascular risk factors among patients with rheumatoid arthritis - Brady, S.; De Courten, B.; Reid, Christopher; Cicuttini, F.; De Courten, M.; Liew, D. (J Rheumatol Publishing Co, 2009)
Objective. People with rheumatoid arthritis (RA) have an increased risk of cardiovascular disease (CVD) compared with the general population. We investigated the relative contribution of traditional cardiovascular risk factors to this elevated risk. Methods. Fifty RA subjects and 150 age and sex matched controls attended a cardiovascular risk assessment clinic between March and July 2006. Traditional cardiovascular risk factors and the absolute risks of CVD (calculated from application of a Framingham risk equation) were compared between the 2 groups. Results. Compared with the controls, RA subjects were more likely to smoke (p < 0.001), be physically inactive (p = 0.006), and have higher mean measurements of body mass index (p = 0.040) and waist circumference (p = 0.049). No significant differences were found in mean levels of plasma lipid or glucose, or in the prevalences of diabetes and hypertension. Overall, the mean absolute risk of CVD was higher in the RA group, even after excluding smokers (p = 0.036). Conclusion. Smoking and physical inactivity are important risk factors in the management of cardiovascular risk among patients with RA. Subjects with RA seem to have higher absolute risks of CVD compared with controls, even independently of smoking. This highlights the importance of treating all modifiable risk factors in those with RA although, individually, few may be conspicuous. The Journal of Rheumatology Copyright © 2009. All rights reserved.